Femoral tunneled hemodialysis catheter insertion through subacutely occluded lower extremity central veins in patients with exhausted vascular access - Çay, Ferdi; Tarı, Onur Ege; Haberal, Güldehan; Eldem, Fatma Gonca (Acta Medica, 2024)
Maintaining venous access and catheter patency in patients undergoing hemodialysis through the central catheter is a dire necessity. When conventional venous accesses have been exhausted, unconventional venous access techniques have become rational options to create vascular access for hemodialysis. Herein, a case with exhausted venous access, that underwent tunneled dialysis catheter insertion through subacutely occluded lower extremity central veins was described.